Evaluation of MRI for diagnosis of extraprostatic extension in prostate cancer. Issue 1 (7th April 2017) - Krishna, Satheesh; Lim, Christopher S.; McInnes, Matthew D.F.; Flood, Trevor A.; Shabana, Wael M.; Lim, Robert S.; Schieda, Nicola
Abstract : Purpose: To assess the ability of magnetic resonance imaging (MRI) to diagnose extraprostatic extension (EPE) in prostate cancer. Materials and Methods: With Institutional Review Board (IRB) approval, 149 men with 170 ≥0.5 mL tumors underwent preoperative 3T MRI followed by radical prostatectomy (RP) between 2012–2015. Two blinded radiologists (R1/R2) assessed tumors using Prostate Imaging Reporting and Data System (PI‐RADS) v2, subjectively evaluated for the presence of EPE, measured tumor size, and length of capsular contact (LCC). A third blinded radiologist, using MRI‐RP‐maps, measured whole‐lesion: apparent diffusion coefficient (ADC) mean/centile and histogram features. Comparisons were performed using chi‐square, logistic regression, and receiver operator characteristic (ROC) analysis. Results: The subjective EPE assessment showed high specificity (SPEC = 75.4/91.3% [R1/R2]), low sensitivity (SENS = 43.3/43.6% [R1/R2]), and area‐under (AU) ROC curve = 0.67 (confidence interval [CI] 0.61–0.73) R1 and 0.61 (CI 0.53–0.70) R2; (k = 0.33). PI‐RADS v2 scores were strongly associated with EPE ( P  < 0.001 / P  = 0.008; R1/R2) with AU‐ROC curve = 0.72 (0.64–0.79) R1 and 0.61 (0.53–0.70) R2; (k = 0.44). Tumors with EPE were larger (18.8 ± 7.8 [median 17, range 6–51] vs. 18.8 ± 4.9 [12, 6–28] mm) and had greater LCC (21.1 ± 14.9 [16, 1–85] vs. 13.6 ± 6.1 [11.5, 4–30] mm); P  < 0.001 and 0.002, respectively. AU‐ROC for size was 0.73 (0.64–0.80) and LCC was 0.69 (0.60–0.76), respectively. Optimal SENS/SPEC for diagnosis of EPE were: size ≥15 mm = 67.7/66.7% and LCC ≥11 mm = 84.9/44.8%. 10 th ‐centile ADC and ADC entropy were both associated with EPE ( P  = 0.02 and < 0.001), with AU‐ROC = 0.56 (0.47–0.65) and 0.76 (0.69–0.83), respectively. Optimal SENS/SPEC for diagnosis of EPE with entropy ≥6.99 was 63.3/75.0%. 25 th ‐centile ADC trended towards being significantly lower with EPE ( P  = 0.06) with no difference in other ADC metrics ( P  = 0.25–0.88). Size, LCC, and ADC entropy improved sensitivity but reduced specificity compared with subjective analysis with no difference in overall accuracy ( P  = 0.38). Conclusion: Measurements of tumor size, capsular contact, and ADC entropy improve sensitivity but reduce specificity for diagnosis of EPE compared to subjective assessment. Level of Evidence: 3 Technical Efficacy: Stage 2 J. Magn. Reson. Imaging 2018;47:176–185.